2016
DOI: 10.1039/c5ra22659g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mo/W codoping on the visible-light photocatalytic activity of monoclinic BiVO4 within the GGA + U framework

Abstract: Mo or W atom doping on V site can form continuum states above conduction band edge of BiVO4. Mo/W/Mo and W/Mo/W co-doped BiVO4 have relatively small formation energies and band gaps, which is particularly suitable for visible-light photocatalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 65 publications
(80 reference statements)
3
26
1
Order By: Relevance
“…For our calculations, we used a supercell of 108 atoms. To encounter the effect of localized electrons, onsite Coulomb repulsions [42] [44]. We have also examined other values for the +U parameter, but the band gap was significantly underestimated.…”
Section: Methodsmentioning
confidence: 99%
“…For our calculations, we used a supercell of 108 atoms. To encounter the effect of localized electrons, onsite Coulomb repulsions [42] [44]. We have also examined other values for the +U parameter, but the band gap was significantly underestimated.…”
Section: Methodsmentioning
confidence: 99%
“…The band position and photoelectric thresholds for several compounds have been calculated. 55,[67][68][69] As regards the Mulliken electronegativity (c) of compound A a -B b C c , it can be calculated according to the following eqn: 70,71 cðA a B b C c Þ ¼ ðcðAÞ a ðBÞ b ðCÞ c Þ 1 aþbþc , where c(A), c(B), and c(C) are the absolute electronegativity of the A atoms, B atoms, and C atoms, respectively; the a, b, c are the number of A atoms, B atoms, C atoms in an A a B b C c compound. Based on the Mulliken denition, per atom's absolute electronegativity is equal to the arithmetic mean of the atomic electron affinity (A) and the rst ionization energy (I).…”
Section: The Band Edge Potentialmentioning
confidence: 99%
“…In addition, the band alignments showed that the F‐doped and BF codoped g‐C 3 N 4 enhanced the oxidation ability, while the B‐doped g‐C 3 N 4 enhanced the reductive ability of g‐C 3 N 4 . The visible light photocatalytic response of W/Mo/W and Mo/W/Mo codoped BiVO 4 was ascribed to the continuum state above the CB edge of BiVO 4 , narrow band gap and smaller formation energies via GGA + U of the Dudarev's method . The BiVO 4 doped with W and Mo enhanced the electron–hole separation without any improvement in the material's optical properties as well as band gap reduction .…”
Section: Recent Progress In the Design Of Semiconductor Photocatalystmentioning
confidence: 99%